The link between individual personality traits and criminality: A systematic review - N. K. Tharshini; Fauziah Ibrahim; Mohammad Rahim Kamaluddin; Balan Rathakrishnan; Norruzeyati Che Mohd Nasir (Multidisciplinary Digital Publishing Institute (MDPI) AG, 2021)
In addition to social and environmental factors, individual personality traits have intricately linked with maladaptive behaviour. Thus, the purpose of this article was to review the link between individual personality traits and criminality. A systematic review was conducted to obtain information regarding the link between individual personality traits with criminal behaviour in the Sage, Web of Science, APA PsycNet, Wiley Online Library, and PubMed databases. The results indicate that individual personality traits that contribute towards criminality are (i) psychopathy; (ii) low self-control; and (iii) difficult temperament. As an overall impact, the review is expected to provide in-depth understanding of the link between individual personality traits and criminality; hence, greater consideration will be given to the dimension of personality as a notable risk factor of criminal behaviour.